Cloning and characterization of a plastidic glycerol 3-phosphate dehydrogenase cDNA from Dunaliella salina - He, Q.; Qiao, D.; Bai, L.; Zhang, Q.; Yang, W.; Li, Q.; Cao, Y.
A cDNA encoding a nicotinamide adenine dinucleotide (NAD+)-dependent glycerol 3-phosphate dehydrogenase (GPDH)has been cloned by rapid amplification of cDNA ends from Dunaliella salina. The cDNA is 3032 base pairs long with an open reading frame encoding a polypeptide of 701 amino acids. The polypeptide shows high homology with published NAD+-dependent GPDHs and has at its N-terminal a chloroplast targeting sequence. RNA gel blot analysis was performed to study GPDH gene expression under different conditions, and changes of the glycerol content were monitored. The results indicate that the cDNA may encode an osmoregulated isoform primarily involved in glycerol synthesis. The 701-amino-acid polypeptide is about 300 amino acids longer than previously reported plant NAD+-dependent GPDHs. This 300-amino-acid fragment has a phosphoserine phosphatase domain. We suggest that the phosphoserine phosphatase domain functions as glycerol 3-phosphatase and that, consequently, NAD+-dependent GPDH from D. salina can catalyze the step from dihydroxyacetone phosphate to glycerol directly. This is unique and a possible explanation for the fast glycerol synthesis found in D. salina
Keywords: DUNALIELLA SALINA; GLYCEROL; GLYCEROL 3-PHOSPHATASE; GLYCEROL 3-PHOSPHATE; DEHYDROGENASE; OSMOTIC STRESS